Using Google Trends to assess COVID-19 related web search behaviour in Arabian Peninsula - Aymane Ajbar; Mourad Boumaaza; Abdelhamid M Ajbar (Journal of Global Health Reports)
# Background The relatively small, populated countries (Bahrain, Kuwait, Oman, Qatar, and the United Arab Emirates) of the Arabian Peninsula have recorded high per-capita COVID-19 infection rates. These countries also have a high internet penetrance rate with a large Google share. Google Trends is a freely accessible online tool that allows the user to analyze trends in public Google searches during a given period and across a specified region. This paper investigates the use of this tool to study public awareness of COVID-19 in the selected countries.